PENGARUH PENGGUNAAN INTERNET DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 7 KUPANG - Maria Legita Pereira Piedade; Data, Ari; Butar-Butar, Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of internet usage and study habits on student learning outcomes. The study used a quantitative approach with an explanatory research method. The population in this study were 167 students of class XI IPS at SMA Negeri 7 Kupang, and the sample in the study amounted to 118 students determined using a sampling technique, namely proportionate stratified random sampling. Data were collected through questionnaires, documentation of student grades, and analyzed using multiple linear regression analysis, classical assumption tests, and hypothesis testing with the help of SPSS version 26.The research results show that internet use and study habits have a positive and significant impact on student learning outcomes, both partially and simultaneously. These findings suggest that appropriate internet use and good study habits can improve student learning outcomes.